Effect of prewarming EDTA blood samples to 37°C on platelet count measured by Sysmex XT‐2000iV in dogs, cats, and horses. (8th July 2016) - Williams, Tim L.; Archer, Joy
Abstract : Background: Pseudothrombocytopenia secondary to platelet clumping is a common cause of preanalytic error for platelet counts in dogs, cats, and horses. In human beings, it is suggested that prewarming blood samples to 37°C prior to hematology analysis will reduce platelet clumping. Objectives: The purpose of the study was to evaluate the effect of prewarming EDTA blood samples to 37°C on measured platelet counts and other hematologic variables. Methods: The EDTA blood samples from dogs, cats and horses submitted to the clinical pathology laboratory at the University of Cambridge were included. Complete blood cell counts performed using a Sysmex XT‐2000iV hematology analyzer were done on samples at room temperature (approximately 22°C) and following warming of the samples to 37°C in a water bath. The Wilcoxon signed rank test was used to compare hematologic variables, including platelet count, before and after sample warming to 37°C. Data are presented as median (25 th, 75 th percentile) increase. Results: Blood samples from 39 dogs, 19 cats, and 10 horses were included. Sample warming to 37°C resulted in a statistically significant increase in platelet counts in dogs (11 [−2, 30] ×10 9 /L), cats (36 [14, 84] ×10 9 /L), and horses (42 [31, 79] ×10 9 /L). Sample warming did not significantly affect other hematologic variables. Conclusions: Prewarming EDTA blood samples to 37°C prior to hematologic analysis increased platelet counts overall in canine, feline, and equine blood, but did not abrogate platelet clumping and pseudothrombocytopenia fully in some cases. Furthermore, true pseudothrombocytopenia was not confirmed in these animals.